2019
DOI: 10.18203/2320-6012.ijrms20195890
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound of umbilical artery in prediction of fetal outcome in pregnancy induced hypertension Sudanese population

Abstract: The pregnancy induced hypertension increase the fetal mortality and morbidity and the using of Doppler umbilical artery indices decrease the fetal mortality and morbidity however, there is few complete data about the most frequently altered Doppler US parameters to predict fetal outcome in pregnancy induced hypertension . Methods This ia cohort prospective study done in two hundred and six women of second and third trimester presenting to antenatal clinic in Soba University Hospital at the department of Obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…Doppler flow ultrasound has emerged as a non-invasive tool for maternal–fetal surveillance in high-risk pregnancies and prediction of adverse-pregnancy outcomes [ 7 ]. Consistent with previous studies [ 20 , 21 ], using Doppler indices for comparison between healthy pregnant females and those with severe LOP showed significant abnormalities in the mean values of all Doppler parameters except MCA PI and RI ( p = 0.783 and 0.423, respectively ). In 2013, Lopez-Mendes et al reported that although the general Doppler results of MCA didn’t show significant difference between preeclamptic and control groups, however, each individual parameter could be used to predict vascular alteration specific for PE [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Doppler flow ultrasound has emerged as a non-invasive tool for maternal–fetal surveillance in high-risk pregnancies and prediction of adverse-pregnancy outcomes [ 7 ]. Consistent with previous studies [ 20 , 21 ], using Doppler indices for comparison between healthy pregnant females and those with severe LOP showed significant abnormalities in the mean values of all Doppler parameters except MCA PI and RI ( p = 0.783 and 0.423, respectively ). In 2013, Lopez-Mendes et al reported that although the general Doppler results of MCA didn’t show significant difference between preeclamptic and control groups, however, each individual parameter could be used to predict vascular alteration specific for PE [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Doppler ow ultrasound has emerged as a non-invasive tool for fetomaternal surveillance in high-risk pregnancies and prediction of adverse-pregnancy outcomes [7]. Consistent with previous studies [20,21], using Doppler indices for comparison between healthy pregnant females and those with severe LOP showed signi cant abnormalities in the mean values of all Doppler parameters except MCA PI and RI (p = 0.783 and 0.423, respectively). In 2013, Lopez-Mendes et al reported that although the general Doppler results of MCA didn't show signi cant difference between preecalmptic and control groups, however, each individual parameter could be used to predict vascular alteration speci c for PE [22].…”
Section: Discussionsupporting
confidence: 81%